Inovasi Digital dalam Bentuk Aset Kripto Sebagai Sarana untuk Melakukan Tindak Pidana Pencucian Uang: - - Amrullah, M Arief (MLJ Merdeka Law Journal, 2024)
This study analyzes the relationship between the development of information technology and the advancement of digital payment tools in the form of Crypto Assets, which have the potential to be exploited by criminals as a means of money laundering. The advancement of information technology has radically transformed modern human life, occurring in almost every country and becoming a global characteristic that eliminates national borders. This indicates a paradigm shift towards an information network that serves as the infrastructure for a country's development. The challenges of globalization lead to a high dependency on other parties and the loss of competitive opportunities due to the limited utilization of information technology. While information technology offers numerous advantages, it also has a dark side that provides space for criminals to operate. For instance, the digitization of assets, including Crypto Assets, is vulnerable or potentially used as a means of money laundering. The lack of regulations in many countries, including Indonesia, creates opportunities that can be exploited by criminals and terrorist financiers. Given that virtual assets (Crypto Assets) offer both significant benefits and potential dangers, it is crucial for countries to take preventive measures by promptly implementing FATF Standards to effectively regulate and supervise this sector.  Keywords: Digital innovation, Crypto Asset, Money Laundering.